Climate and ancient societies (Copenhagen)
351, [1] s.
Keywords: "Climate and human responses to it have a strongly interconnected relationship. Thus when climate change occurs, the result of either natural or human causes, societies should react and adapt to these. But do they? If so, what is the nature of that change, and are the responses positive or negative for the long-term survival of social groups? In Climate and Societies, scholars from diverse disciplines includ-ing archaeology, geology and climate sciences explore scientific and material evidence for climate changes in the past, their causes, their effects on ancient societies and how those societies responded. Organized around four key themes each dealing with ways to understand past climates, human impact, and sustainability – holocene climate reconstruction; responses of complex societies to climatic variation; Archaeological evidence for pollution and its ecological implica-tions; and stable isotope analysis in the Middle East – the chapters demonstrate the value of a longue durée perspective on a topic of crucial importance to the future of our planet." --